Heterotrophic Bacteria Enhance the Aggregation of the Marine Picocyanobacteria Prochlorococcus and Synechococcus - Cruz, Bianca N.; Neuer, Susanne (Frontiers in Microbiology, 2019)
Marine picocyanobacteria are ubiquitous primary producers across the world’s oceans, and play a key role in the global carbon cycle. Recent evidence stemming from in situ investigations have shown that picocyanobacteria are able to sink out of the euphotic zone to depth, which has traditionally been associated with larger, mineral ballasted cells. The mechanisms behind the sinking of picocyanobacteria remain a point of contention, given that they are too small to sink on their own. To gain a mechanistic understanding of the potential role of picocyanobacteria to carbon export, we tested their ability to form “suspended” (5-60 µm) and “visible” (ca. > 0.1 mm) aggregates, as well as their production of transparent exopolymer particles (TEP)—which are a key component in the formation of marine aggregates. Additionally, we investigated if interactions with heterotrophic bacteria play a role in TEP production and aggregation in Prochlorococcus and Synechococcus by comparing xenic and axenic cultures. We observed TEP production and aggregation in batch cultures of axenic Synechococcus, but not in axenic Prochlorococcus. Heterotrophic bacteria enhanced TEP production as well as suspended and visible aggregate formation in Prochlorococcus, while in Synechococcus, aggregation was enhanced with no changes in TEP. Aggregation experiments using a natural plankton community dominated by picocyanobacteria resulted in aggregation only in the presence of the ballasting mineral kaolinite, and only when Synechococcus were in their highest seasonal abundance. Our results point to a profoundly different export potential between the two picocyanobacteria, which may be mediated by interactions with heterotrophic bacteria and presence of ballasting minerals. Biological aggregation and re-packaging as a result of grazing by zooplankton are more likely mechanisms for significant sinking and export of picocyanobacteria cells in situ.